Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1017/s0954579417000189
|View full text |Cite
|
Sign up to set email alerts
|

Testing the limits: Extending attachment-based intervention effects to infant cognitive outcome and parental stress

Abstract: Using a sample of 41 infants and toddlers (21 interventions, 20 controls) who were neglected or at serious risk for neglect, this randomized clinical trial examined the efficacy of a parent-child attachment-based video-feedback intervention on parental sensitivity, parental stress, and child mental/psychomotor development. Results showed that following the 8-week intervention, scores for maternal sensitivity and child mental and psychomotor development were higher in the intervention group than in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…The research featured in this Special Issue clearly pushes the boundaries of the status quo of attachment-based intervention in a number of potentially generative ways. Three of the reports find efficacy of attachment-related intervention not merely for interpersonal outcomes (as might be expected) but for improving aspects of cognitive development (Cassidy et al, 2017;Dubois-Comtois et al, 2017;Lind, Raby, Caron, Roben, & Dozier, 2017). Another interesting report based on a French sample hones in on some of the specific interpersonal behavioral change mechanisms (i.e., improvements in disrupted maternal communication) by which attachmentinformed home visitations offset risk for disorganized attachment (Tereno et al, 2017).…”
Section: Attachment Interventionsmentioning
confidence: 92%
See 2 more Smart Citations
“…The research featured in this Special Issue clearly pushes the boundaries of the status quo of attachment-based intervention in a number of potentially generative ways. Three of the reports find efficacy of attachment-related intervention not merely for interpersonal outcomes (as might be expected) but for improving aspects of cognitive development (Cassidy et al, 2017;Dubois-Comtois et al, 2017;Lind, Raby, Caron, Roben, & Dozier, 2017). Another interesting report based on a French sample hones in on some of the specific interpersonal behavioral change mechanisms (i.e., improvements in disrupted maternal communication) by which attachmentinformed home visitations offset risk for disorganized attachment (Tereno et al, 2017).…”
Section: Attachment Interventionsmentioning
confidence: 92%
“…First, even the largest interventions reported in this Special Issue (e.g., Cassidy et al, 2017;Humphreys et al, 2017;Lind et al, 2017) consisted of fewer than 200 participants, with adequate power to detect only medium or larger population effects. In contrast, many of the studies reported here included approximately 100 participants, and a handful of "proof of concept" reports were based on fewer than 50 individuals (e.g., Dubois-Comtois et al, 2017;Schact et al, 2017;Swain et al, 2017). Intervention research presents inherent challenges and is immensely expensive and time consuming, but the point remains that only large sample trials are capable of detecting the kinds of small (though ideally enduring) differences between intervention and control groups that might be reasonably expected in this area.…”
Section: Attachment Interventionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our work with adolescent mothers and other high‐risk mother–infant dyads, as well as randomized clinical trials conducted with children receiving child protection services, either with foster or biological families has shown that a positive, warm, and supporting mentoring relationship with parents, using a structured and encouraging approach to modifying parent–child interaction, can lead to improvements in maternal interactive behavior, the emerging parent–child relationship, and child outcomes. Benefits of AVI include improvements in maternal sensitivity (the specific target of the intervention), attachment, child cognitive and motor development for infants and toddlers, and a reduction in parental perceptions of preschooler externalized behavior (Dubois‐Comtois et al., ; Moss et al., ; Moss et al., ). Recent work with child protection agencies show reduced levels of child placement when dyads are exposed to AVI (Tarabulsy, Baudry, Pearson, & Turgeon, ).…”
Section: Introductionmentioning
confidence: 99%
“…intervention studies have shown to be effective in improving child attachment (i.e., fewer children with a disorganized attachment and more children with a secure attachment post-intervention), child mental and motor development (Dubois-Comtois et al, 2017) and parent-child interactive quality, and in reducing emotional and behavioural problems (Bernard et al, 2012;Moss et al, 2011;Negrao et al, 2014).…”
mentioning
confidence: 99%